Ottoman law of war and peace - Panaite, Viorel, 1958- author.
1 online resource.
Keywords: Making use of legal and historical sources, Viorel Panaite analyzes the status of tribute-payers from the north of the Danube with reference to Ottoman law of peace and war. He deals with the impact of Ottoman holy war and the way conquest in Southeast Europe took place; the role of temporary covenants, imperial diplomas and customary norms in outlining the rights and duties of the tributary princes; the power relations between the Ottoman Empire and the tributary-protected principalities of Wallachia, Moldavia and Transylvania. He also focuses on the legal and political methods applied to extend the pax ottomanica system in the area, rather than on the elements that set these territories apart from the rest of the Ottoman Empire.